1993
DOI: 10.1111/j.1365-2249.1993.tb05916.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for iC3 generation during cardiopulmonary bypass as the result of blood-gas interaction

Abstract: SUMMARYEarlier we have shown that iC3 is getieraled at the blood-gas interface in vitro and that the generation of this molecule is independent orcotnplemcnt activation and the composition ofthe gas. In order to investigate whether iC3 is also generated during cardiopulmonary bypass where blood comes into contact with oxygen bubbles, two bubble oxygenators were ineubated at 37 C with human heparinized blood. A continuous increase in the level of iC3 was shown in the oxygen-perfused bubble oxygenator(upto 100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 29 publications
1
19
0
3
Order By: Relevance
“…factor H). It has previously been demonstrated that by this definition, C3(H 2 O) occurs on polystyrene surfaces [52], on human platelets [53], and at blood-gas [54] and plasmae–gas interfaces [8]. The polystyrene surface and the platelet membrane are solid surfaces when compared to the variable surfaces formed by gas bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…factor H). It has previously been demonstrated that by this definition, C3(H 2 O) occurs on polystyrene surfaces [52], on human platelets [53], and at blood-gas [54] and plasmae–gas interfaces [8]. The polystyrene surface and the platelet membrane are solid surfaces when compared to the variable surfaces formed by gas bubbles.…”
Section: Discussionmentioning
confidence: 99%
“…Complement factor C3, a downstream factor of MASP-2, was reported to be activated in peripheral circulation in patients undergoing open heart surgery with CPB [30, 31], and was associated with pathogenic post-operation conditions [32–36]. It has been reported that post-operative peak cTnI >13ng/ml was an independent predictor of short and mid-term clinical outcome after cardiac surgery [37].…”
Section: Discussionmentioning
confidence: 99%
“…This form of C3 has C3b-like properties, in that it is capable of binding factor B and factor H and of forming a fluid-phase AP convertase (Pangburn and Müller-Eberhard, 1983;Pangburn et al, 1981). We have previously demonstrated the generation of C3(H 2 O) in vitro when gas is bubbled through whole blood (Ekdahl et al, 1992), and in vivo during CPB to a maximal level of 100 nM, which corresponds to hydrolysis of approximately 1% of the total pool of C3 (Pekna et al, 1993). This result indicates that the molecular ratio between C3(H 2 O) and factor B in vivo would be 1:20 (0.1:2 μM), and it is thus reasonable to postulate that the equilibrium in that situation would favor the formation of C3(H 2 O)/Bb convertase in the fluid phase.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction constantly takes place at a low rate (tickover) in blood (Pangburn and Müller-Eberhard, 1983;Pangburn et al, 1981). We have demonstrated the generation of C3(H 2 O) at the interface between blood and gas in an in vitro model of cardiopulmonaty bypass (CPB) and in vivo in patients during CPB (Ekdahl et al, 1992;Pekna et al, 1993).…”
Section: Introductionmentioning
confidence: 99%